Case Report: A recurrent case of ALK-ALCL after autologous transplantation was successfully treated with BV + a modified CHEP chemotherapy containing mitoxantrone hydrochloride liposome with the addition of chidamide maintenance therapy - Shang, Zhen; Zhang, Qi; Liu, Wanying; Wu, Jiaying; Zhang, Yicheng; Xiao, Yi (Frontiers in Oncology, 2023)
BACKGROUND: ALK-negative anaplastic large cell lymphoma (ALK-ALCL) is a rare heterogeneous malignancy of T-cell origin.ALK- ALCL has a poor prognosis, with more patients experiencing relapses and refractory to treatment, and its treatment remains challenging. We report a case with bone involvement as the main clinical manifestation of recurrent, and the patient achieved significant partial remission after brentuximab vedotin(BV) combined with a modified CHEP chemotherapy containing mitoxantrone hydrochloride liposome (PLM60) with the addition of chidamide maintenance therapy and received regular follow-up, with a disease-free survival of 16 months to date. A literature review of the clinical presentation and treatment of ALCL was also conducted to identify strategies for its diagnosis and management. CONCLUSIONS: ALK-ALCL with bone involvement as the main manifestation of recurrent is relatively rare. Here, BV combined a modified CHEP chemotherapy containing mitoxantrone hydrochloride liposome was applied for the first time in a patient with relapsed ALK-ALCL, inducing remission and extending survival. However, further prospective studies with many patients are needed to determine the biological characteristics of this rare type of ALK-ALCL and relevant treatment strategies.